Susceptibility to Alcohol Hangovers: Not Just a Matter of Being Resilient. (4th December 2017) - van Schrojenstein Lantman, Marith; van de Loo, Aurora J A E; Mackus, Marlou; Kraneveld, Aletta D; Brookhuis, Karel A; Garssen, Johan; Verster, Joris C
Abstract: Introduction: Although most drinkers have experienced a hangover the day following heavy alcohol consumption, a minority claims to be hangover resistant despite consuming the same large quantities of alcohol as those reporting alcohol hangover. The aim of the current study was to examine if susceptibility to experiencing hangovers is related to a drinker's interpretation of wellbeing and psychological assets to bounce back. Methods: A survey was conducted among 2295 Dutch students assessing their past month alcohol consumption patterns, and measuring mental resilience and wellbeing. Estimated peak blood alcohol concentration (e-pBAC) for their heaviest drinking occasion in the past month was computed for each participant. Data from participants who reported a past month hangover, i.e. hangover sensitive drinkers, were compared with hangover resistant drinkers. The analyses were conducted for (a) all participants reaching an e-pBAC ≥ 0.11% ( N = 986, of which 24.6% claimed to be hangover resistant) and (b) participants reaching an e-pBAC ≥ 0.18% ( N = 480, of which 16.7% claimed to be hangover resistant). Results: For both e-pBAC cut-off values, no significant differences between hangover sensitive and hangover resistant drinkers were found for mental resilience and wellbeing. Conclusion: The current findings suggest that having a hangover is not simply an expression of poor psychological coping with the next-day consequences of heavy alcohol consumption.